The effects of first-trimester hemoglobin on adverse pregnancy outcomes - Özgen, Gülten; Adanas, Gültekin; Özgen, Levent (Journal of Surgery and Medicine, 2020)
Aim: Previous studies have demonstrated that variable hemoglobin levels are associated with adverse pregnancy outcomes such as postpartum hemorrhage, pregnancy-induced hypertension, intrauterine growth restriction, gestational diabetes mellitus and perinatal mortality. Here, we aimed to investigate the effects of hemoglobin (Hb) levels measured in the first trimester of pregnancy on pregnancy outcomes and identify the predictive value of Hb on adverse pregnancy outcomes. Methods: This single-center, retrospective study included a total of 8,916 pregnant women who were diagnosed, followed, and delivered their babies in our Obstetrics and Gynecology clinic. The patients were divided into three groups according to their Hb levels as anemic (Hb <11 g/dL, n=1,846), normal (Hb <12.5 g/dL, n=4,898), and elevated (Hb ≥12.5 g/dL, n=2,172). Demographic and clinical features of the patients were obtained from hospital records. Adverse pregnancy outcomes were also noted. Results: The mean age of the patients was 27.50 (4.45) years and BMI value was 25.03 (3.39) kg/m2. The mean Hb level was 11.83 (0.88) g/dL and the mean hematocrit value was 36.004 (2.75%). Irrespective of Hb levels, among all patients, rate of pregnancy loss was 6.5%, rate of impaired glucose tolerance, 4.9%, gestational diabetes mellitus, 5.1%, pregnancy-induced hypertension, 7.4%, preterm birth 3.8%. The rate of newborns in need of neonatal intensive care unit was 3.5%, while 3.8% were born with low APGAR scores. Placenta previa was observed in 2.4% of patients, and placental abruption was seen in 1.3%. About 39.3% had a cesarean-section (C/S) delivery, 5.9% gave birth to low birth-weight neonates, and premature rupture of membranes was observed in 9.7% patients. There were no significant differences with respect to adverse pregnancy outcomes between the three groups (P>0.05 for all). Conclusion: Our study results showed no significant differences between the three groups categorized by Hb concentrations measured in the first trimester in terms of adverse pregnancy outcomes.